Analisis Pelaksanaan Supervisi Kinerja Guru di SDN 11 Pasui Kecamatan Bungoro Kabupaten Pangkep - Tahir, Sri Ratna; Yunus, Muh; W, Muhammad Fahreza (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This study aims to analyze in depth the implementation of teacher performance supervision at SDN 11 Pasui, Bungoro District, Pangkep Regency. The primary focus of this research is to evaluate the methods and approaches used in supervision, as well as to identify the impact of the process on teacher competence, professionalism, and the quality of learning. Furthermore, this study also aims to explore various supporting and inhibiting factors and to formulate strategic recommendations to optimize the supervision system at the school. The research method employed is a qualitative approach with a case study design. Data were collected through triangulation techniques, including participatory observation of the learning process and supervision interactions, in- depth interviews with key informants (Principal, Teachers, and School Supervisors), and documentation studies of supervision plans and reports. Data analysis was carried out inductively using the Miles and Huberman interactive model, which consists of data collection, data condensation, data display, and conclusion drawing. The results of the study indicate that the implementation of supervision at SDN 11 Pasui has transformed from a mere administrative formality into a systematic, humanistic, and collaborative professional development process. Supervision is conducted routinely through pre-observation, observation, and post-observation stages, with a primary focus on improving pedagogical competencies such as subject matter mastery and classroom management. Despite obstacles such as time constraints and administrative burdens, the application of coaching strategies and reflective dialogue has proven effective in significantly increasing motivation, self-reflection abilities, and the quality of teacher instruction.